Deletion of cas3 gene in Streptococcus mutans affects biofilm formation and increases fluoride sensitivity. (March 2019) - Tang, Boyu; Gong, Tao; Zhou, Xuedong; Lu, Miao; Zeng, Jumei; Peng, Xian; Wang, Shida; Li, Yuqing
Highlights: The S. mutans cas3 deletion strain formed weak biofilm. Deletion of cas3 gene in S. mutans increased fluoride sensitivity. S. mutans lacking cas3 became less competitive under fluoride treatment. Abstract: Objective: The goal of this study was to analyze the impact of cas3 gene on the biofilm formation and virulence gene expression in S. mutans, since our previous studies have found a connection between CRISPR/Cas systems and biofilm formation in S. mutans . Methods: The cas3 gene in-frame deletion strains of S. mutans UA159 was constructed by a two-step transformation procedure and the cas3 mutant strain was complemented in trans . The biofilm biomass was measured by crystal violet staining, and the synthesis of exopolysaccharides (EPS) was measured by the anthrone-sulfuric method. Biofilm analysis and structural imaging was using confocal laser scanning microscope (CLSM) and scanning electron microscope (SEM) assays. The fluorescence in situ hybridization (FISH) was used to analyze the spatiotemporal interactions between S. mutans and Streptococcus sanguinis . Fluoride sensitivity was determined using fluoride tolerance assays. The expression of biofilm formation related genes was evaluated by qRT-PCR. Results: Our results showed that S. mutans cas3 deletion strain formed less biofilm and became less competitive when it was co-cultured with S. sanguinis under fluoride treatment. The expression levels of virulence genes including vicR, gtfC, smu0630 and comDE were significantly downregulated. Conclusions: The cas3 gene in S. mutans could regulate biofilm formation and fluoride resistance, consequently affecting S. mutans competitiveness in a dual-species biofilm model under fluoride treatment. These results also provide a potential strategy for enhancing fluoride specificity, with cas3 gene as a potential genetic target in the modulation of oral microecology and the treatment of dental caries.